The call of the wild : he had learned well the law of club and fang - London, Jack, 1876-1916 (London : Sirius, 2020)
The adventures of an unusual dog, part St. Bernard, part Scotch shepherd, that is forcibly taken to the Klondike gold fields where he eventually becomes the leader of a wolf pack.
Publishers Weekly
8.
6-12.
Y
1120
Guided Reading
Keywords: Dogs -- Fiction; Wolves -- Fiction; Adventure and adventurers -- Fiction; Yukon Territory -- Fiction